Endosomal phosphatidylserine is critical for the YAP signalling pathway in proliferating cells. Issue 1 (December 2017) - Matsudaira, Tatsuyuki; Mukai, Kojiro; Noguchi, Taishin; Hasegawa, Junya; Hatta, Tomohisa; Iemura, Shun-ichiro; Natsume, Tohru; Miyamura, Norio; Nishina, Hiroshi; Nakayama, Jun; Semba, Kentaro; Tomita, Takuya; et al.
Abstract Yes-associated protein (YAP) is a recently discovered growth-promoting transcription coactivator that has been shown to regulate the malignancy of various cancers. How YAP is regulated is not fully understood. Here, we show that one of the factors regulating YAP is phosphatidylserine (PS) in recycling endosomes (REs). We use proximity biotinylation to find proteins proximal to PS. Among these proteins are YAP and multiple proteins related to YAP signalling. Knockdown of ATP8A1 (an RE PS-flippase) or evectin-2 (an RE-resident protein) and masking of PS in the cytoplasmic leaflet of membranes, all suppress nuclear localization of YAP and YAP-dependent transcription. ATP8A1 knockdown increases the phosphorylated (activated) form of Lats1 that phosphorylates and inactivates YAP, whereas evectin-2 knockdown reduces the ubiquitination and increased the level of Lats1. The proliferation of YAP-dependent metastatic cancer cells is suppressed by knockdown of ATP8A1 or evectin-2. These results suggest a link between a membrane phospholipid and cell proliferation. Yes-associated protein (YAP) is a growth-promoting transcription co-activator that regulates the malignancy of various cancers, however its regulation is not fully understood. Here the authors show that phosphatdylserine at recycling endosomes regulates YAP signalling pathway.